By design : planning research on higher education - Light, Richard J.; Singer, Judith D.; Willett, John B. (Cambridge, Mass. ; London : MIT, 1990)
Why do research on higher education?
What are your questions?
Correlation versus causation
What groups do you want to study
Specifying the target population
Where should you conduct the study?
Selecting your sample
What predictors do you want to study?
The important role of variation
Compared to what?
Randomized control groups: The best comparisons
What are your outcomes?
Short-term versus long-term effects
How can you improve your measures?
Reliability and measurement error
Six strategies for improving measurement quality
How many people should you study?
Instrument precision and sample size
Should you try it out on a small scale?
The advantages of pilot studies
Where should you go from here?
Planning a longer-term research program
Str. 245-272: Bibliografija
Kazalo
Keywords: edukacijska psihologija; visoko obrazovanje; metodologija istraživanja